Emotions and eye-tracking of differing age groups searching on e-book wall. Issue 4 (16th July 2018) - Wu, Ko-Chiu; Huang, Yi-Hsieh
Abstract : Purpose: The purpose of this paper is to explore the effects of a large e-book touch-wall, on which the visualized interface provides information in a fun, hedonic-oriented fashion on readers of different ages browsing in a public library. The authors examined how emotions exert influence on the information-seeking behaviors of readers. Design/methodology/approach: The authors investigated the emotions and responsive eye movements of 38 readers in various age groups when operating the touch-wall interface of New Taipei City Library. They were monitored using an eye-tracker and a camera that videotaped their spontaneous facial expressions. A facial affect scoring technique was used to measure emotions and statistical analysis was used to explore the relationships among the scope of eye movements, emotions and information-seeking behavior of readers of different ages. Findings: Results revealed that participants experienced an array of emotions, such as contemplative, doubtful or peaceful. The older the participant was, the smaller the scope of eye movements was. Scope was also affected by emotions (both positive and negative). Originality/value: These results serve as useful reference for exploration into human – information interaction, perceived ease of use, affected searching and the formulation of knowledge structures in visualized interfaces.